PRODUKSI ETANOL MENGGUNAKAN Saccharomyces cerevisiae POLIPLOID YANG DIIMMOBILISASI NA-ALGINAT DAN KALSIUM KLORIDA - Muhammad Thamrin Hidayat, ; Gatot Suparno, (Matematika dan Sains, 2009)
The aim of research was to know the ability of polyploid Saccharomyces cerevisiae immobilized on mixture of Na-alginat and CaCl2 to conduct fermentation process to produce ethanol higher. Fermentation process was carried out twice namely for 48 hours and 96 hourrs. The results showed that the higher ethanol concentration was produced at the first and the second fermentation of 48 hours as much as 9.603%. While the first fermentation of 96 hours produced 6.987%2 to conduct fermentation process to produce ethanol higher. Fermentation process was carried out twice namely for 48 hours and 96 hourrs. The results showed that the higher ethanol concentration was produced at the first and the second fermentation of 48 hours as much as 9.603%. While the first fermentation of 96 hours produced 6.987%